The Role of Effective Leadership in Achieving Administrative Creativity among Employees: A Field Study in the General Directorate of Vocational Education at the Ministry of Education in Iraq (Entrepreneurship Journal for Finance and Business, 2023)
The research mainly seeks to strengthen the relationship between the variables of the current study represented by skillful leadership with its dimensions (open and closed) and administrative creativity represented by its dimensions (Originality، flexibility، fluency، feeling the problem، the ability to analyze) to identify the role it plays within the directorates of education in Iraq.The study population is represented by the directorates of the Iraqi Ministry of Education، and due to the difficulty of determining the total number of the study community، the research sample was deliberately selected on the basis of the administrative positions in the General Directorate of Vocational Education / Iraq on the members of the community، who are managers، their assistants، department managers and divisions، as they are academically and professionally qualified and represent the level of senior and middle management that leads Work and workers in the directorateAfter the researcher analyzed the data and tested the hypotheses, the main conclusion was reached and its content is: “There is a role for skilled leadership in its dimensions (open and closed) on administrative creativity represented by the dimensions (authenticity, flexibility, fluency, sense of the problem, ability to analyze) in the Iraqi education directorates. It was adopted the researcher used the questionnaire as a main tool for collecting data from the sample. The total sample amounted to (195) individuals. The measurement tools represented by the Cronbach alpha coefficient and the statistical description, which includes the arithmetic mean and the standard deviation, were used. Hypotheses were tested based on the simple correlation coefficient (Pearson) and the statistical program was used. (SPSS).